2001
DOI: 10.1093/carcin/22.9.1543
|View full text |Cite
|
Sign up to set email alerts
|

Role of PKC and MAP kinase in EGF- and TPA-induced connexin43 phosphorylation and inhibition of gap junction intercellular communication in rat liver epithelial cells

Abstract: Gap junction intercellular communication (GJIC) is involved in the regulation of many cellular processes. The gap junction channels are made up of connexins and the flow of polar low molecular weight molecules through these channels is inhibited by several groups of substances, such as tumour promoters and growth factors. The phorbol ester 12-O-tetradecanoylphorbol 13-acetate (TPA), chlordane and the growth factor epidermal growth factor (EGF) are potent inhibitors of GJIC in several cell types, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 55 publications
8
91
1
Order By: Relevance
“…In our previous study, ERK-and p38 MAP kinase inhibitors were found to prevent the inhibition of GJIC induced by TPA and H 2 O 2 [1,9]. TPA has been reported to induce the inhibition of GJIC [11,18], and the inhibition of GJIC by TPA which likely contributes to alterations of growth, differentiation, and apoptosis [21]. Furthermore, differential regulation of Cx43 expres- Fig.…”
Section: Discussionmentioning
confidence: 92%
“…In our previous study, ERK-and p38 MAP kinase inhibitors were found to prevent the inhibition of GJIC induced by TPA and H 2 O 2 [1,9]. TPA has been reported to induce the inhibition of GJIC [11,18], and the inhibition of GJIC by TPA which likely contributes to alterations of growth, differentiation, and apoptosis [21]. Furthermore, differential regulation of Cx43 expres- Fig.…”
Section: Discussionmentioning
confidence: 92%
“…, not on tyrosine, but serine amino acids (Hossain, Ao, & Boynton, 1998a;Kanemitsu & Lau, 1993;Lau, Kanemitsu, Kurata, Danesh, & Boynton, 1992;Rivedal & Opsahl, 2001). The disruption of gap junctional communication appeared to occur independently of observable changes in gap junction plaques (Lau et al, 1992).…”
Section: Receptor Protein Tyrosine Kinases-in Many Cases Activation mentioning
confidence: 98%
“…Several studies have focused on using growth factors and PMA in combination with MAPK and PKC inhibitors to correlate changes in Cx43 isoform migration with shutdown of gap junctional communication. In one study, IAR6.1 cells, which endogenously express Cx43 and make P2 in resting cells, exhibited a decrease in gap junctional communication and a migration shift in response to both PMA and EGF (Rivedal & Opsahl, 2001). In these cells, inhibition of ERK1/2 but not PKC inhibition could inhibit the migration shift in response to PMA and EGF, although it did not reverse PMA induced inhibition of gap junctional communication.…”
Section: Induced Phosphorylation Can Lead To a Distinct P2mentioning
confidence: 99%